Creation of Coping-Profiles of Managers for Obtaining Methods of Coping in Socially Significant Situations during Negotiations - Gurieva, Svetlana D.; Zashchirinskaia, Oksana V.; Udavikhina, Uliana A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Professional activity of managers, entrepreneurs and other persons who often enter into negotiations implies high density of difficulties and problem situations. This study explored whether social and psychological peculiarities of personality preferred negotiating styles and response to ambiguity may be determinants of productive coping behaviour. The authors surveyed 105 managers of medium and large-sized business aged from 23 to 59. The average age of the respondents is 35.37 years. The study measured an adaptive level of coping strategies by E. Heim's Coping Questionnaire, peculiarities of personality by 5PFQ P. Costa and R. McCrae, preferred negotiating styles and response to ambiguity. Results suggested that adaptive coping strategies more frequently used by less anxious, emotionally healthy managers who in dealing with colleagues and subordinates show respect, willingness to understand and accept the other's point of view, comparative to non-adaptive or relatively adaptive coping strategies using managers with high anxiety, emotional instability and less developed communication skills. It was found the correlation between preferences of the negotiation styles and personality characteristics of respondents. Managers who use adaptive behavioural coping techniques in socially significant and stressful situations are characterized by a higher degree of respect for the people around them (p<0.001), greater emotional relaxation (p<0.001). These social and psychological characteristics may be considered as the determinants of a person's use of adaptive coping ways under challenging situations and more or less serve as a guarantee for their successful overcoming.